Process Modeling in the Operating Room: A Socio‐Technical Systems Perspective. Issue 3 (29th August 2016) - Bonzo, Sarah M.; McLain, David; Avnet, Mark S.
ABSTRACT: Given the importance of communication in healthcare, a need exists for modeling approaches that facilitate analysis of complex interactions among providers. While attempts have been made to translate best practices from engineering, manufacturing, and other fields, their value has been limited because they are applied with minimal modification for contextual differences in healthcare. This paper develops a methodology for modeling processes and analyzing communication in a particular healthcare setting, the hospital operating room (OR). The analysis is based on the construction of a large multidomain matrix (MDM), a representation of interactions across "domains" in a socio‐technical system. In the OR, these domains are people (the surgical team) and process (the steps that they take in a surgical procedure). Based on these domains, the MDM consists of four quadrants: a process architecture design structure matrix (DSM) representing task dependencies, an organization architecture DSM representing interactions among staff, a domain mapping matrix (DMM) of activities performed by team members, and a DMM of activities that "trigger" team members to complete their own tasks. Integrated analysis of these matrices leads to a process map of surgical procedures and construction of a congruence matrix specifying the relationship between expected and actual interactions in the OR. Analysis of process metrics demonstrate that merely engaging the surgical staff in building the MDM can itself lead to performance improvement. The paper lays the foundation for future studies focused on understanding the relationship of team communication to patient outcomes in a single OR and across healthcare systems.